(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
This article analyzes the transport logistics of member states of the World Trade Organization (WTO) and studies its role in Gross Domestic Product (GDP). It examines how joining the WTO impacts transport and logistics systems, the effectiveness of free trade conditions, the significance of integration into international supply chains, and factors influencing the development of transport infrastructure. The article provides an in-depth analysis of export development, modernization of transport systems, and their contribution to GDP through WTO membership. It also highlights how the growth of international trade, opening of new markets, and improvement of transport systems influence a country’s economic growth. This paper helps deepen understanding of the relationship between transport logistics and economic development and serves as a useful guide for determining strategic development paths for WTO member countries.[2]